Bilateral symmetry in lower extremity mechanics during stair ascent and descent following a total hip arthroplasty: A one-year longitudinal study. Issue 1 (January 2015) - Queen, Robin M.; Attarian, David E.; Bolognesi, Michael P.; Butler, Robert J.
Abstract Background Total hip arthroplasty is the standard treatment to reduce pain and improve function in people with advanced hip osteoarthritis; however, persisting asymmetrical gait patterns have been identified in level walking. Therefore, this study evaluated limb asymmetries during stair ascent and descent in patients pre-operatively through 1 year after a hip replacement. It was hypothesized that lower extremity mechanics would improve on the surgical side, but asymmetries would persist through one year. Methods Kinematics and kinetics were collected during seven ascending and descending trials pre-operatively, 6 weeks, and 1 year post-operatively for 42 hip replacement patients. Data were analyzed using 2 ∗ 3 (Limb ∗ Time) within-subject repeated measures analyses of variance (ANOVAs) to determine significant differences between limbs across time (P < .05). Findings Significant changes across time, independent of limb included: peak hip flexion, extension, and adduction during ascent. Peak hip flexion and extension, hip flexion moment, adduction and abduction moments, and propulsive vertical ground reaction force were different during descent (P < .05). Independent of time, significant asymmetries between limbs were observed in peak hip flexion, hip abduction, and hip extension moments during ascent, and in peak hip abduction moment during descent (P < .05). Interpretation Abnormal movement patterns on the surgical side increase demands on other joints and could lead to permanent joint damage. These side-to-side differences in joint mechanics should be addressed during the early post-operative period through additional interventions in an attempt to normalize the differences and potentially improve long-term joint health throughout the lower extremity.